Proud to Be British - Broomfield, Nick (Lafayette Film, 1973)
Examines the way of life of the southern area of Britain known variously as the 'Home counties' and the 'stock-broker belt'. Suggests that the inhabitants of the region cling to a way of life reminiscent of the time when Britain was at the 'peak of the achievement' during the colonial era. Shows that nationalistic sentiments are passed on and reiterated by the younger generation.